2021
DOI: 10.1002/cncr.33462
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and modified Glasgow Prognostic Score predict postsurgical outcomes in localized renal cell carcinoma

Abstract: BACKGROUND: Body composition and inflammation are gaining importance for prognostication in cancer. This study investigated the individual and combined utility of the preoperative skeletal muscle index (SMI) and the modified Glasgow Prognostic Score (mGPS) for estimating postoperative outcomes in patients with localized renal cell carcinoma (RCC) undergoing nephrectomy. METHODS: The authors performed a retrospective review of 352 patients with localized RCC. SMI was measured via computed tomography or magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…5,6 In addition, there are several quantifiable instruments such as sarcopenia and the Eastern Cooperative Oncology Group performance status that can measure physical health to some extent. Sarcopenia has been found to be associated with worse survival in patients with localized renal cell carcinoma, 7 and this is in line with the current article. These measures of physical health can be compared with self-reported QOL metrics in prospective studies to help to define the predictive value of each instrument.…”
supporting
confidence: 89%
“…5,6 In addition, there are several quantifiable instruments such as sarcopenia and the Eastern Cooperative Oncology Group performance status that can measure physical health to some extent. Sarcopenia has been found to be associated with worse survival in patients with localized renal cell carcinoma, 7 and this is in line with the current article. These measures of physical health can be compared with self-reported QOL metrics in prospective studies to help to define the predictive value of each instrument.…”
supporting
confidence: 89%
“…As the authors state, findings show that deficiencies in muscle mass are independently associated with relevant short-term clinical outcomes (complications, functional deficits, systemictherapy-associated adverse events) and long-term clinical outcomes (cancer-specific and all-cause mortality) across malignancies. [7][8][9] These results are consistent with those from prior cohorts of patients with localized RCC (pT1-4 Nx/0) 10,11 treated surgically and those from patients with metastatic RCC treated with cytoreductive nephrectomy. 12 Other authors have observed an association between sarcopenia and postoperative surgical complications, but not overall survival.…”
supporting
confidence: 85%
“…15 Second, the relationships between observations of muscle loss and potentially additive risk factors such as malnutrition, low activity, and multimorbidity remain to be fully characterized, as well as key outcomes beyond survival such as physical function, independence, cognition, and quality of life. 11,16,17 Finally, numerous outstanding methodologic questions are saliant for the continued pursuit of high-quality body composition research. One key knowledge gap is associated with the need to describe robust population-based body composition norms across racial and ethnic groups, ages, and disease states.…”
mentioning
confidence: 99%
“…Our findings expand the evidence relating muscle mass to cancer‐specific survival. The muscle area on abdominal CT at the level of the third lumbar vertebral body is an established predictor of cancer‐specific survival following resection of infra‐diaphragmatic malignancies 24–28 . Psoas muscle area on preoperative abdominal CT has also been linked to OS in patients with lung cancer in a single‐center study 12 .…”
Section: Discussionmentioning
confidence: 99%